IMPROVING ENGLISH VOCABULARY MASTERY THROUGH TALKING STICK STRATEGY AT THE TENTH GRADE STUDENTS OF SMA NEGERI 1 KASIMBAR - wahyu alansah; Nurasmawati; Ana Kuliahana (Datokarama English Education Journal, 2021)
Students usually feel bored in vocabulary lesson because they have less vocabulary and the teacher used same strategy in every meeting. In learning vocabulary, it is important used attractive strategy in order to the students interest to learn vocabulary. This research focuses on the using of talking stick strategy to the tenth grade students’ vocabulary mastery at SMA Negeri 1 Kasimbar. The researcher applied quasi experimental research design and need pre-test and post-test to both experimental and control class. The pre-test was to know the level of students’ vocabulary mastery ability before giving treatment while the post-test was used to know the result after giving treatment. There was a significant difference score of the post-test of the experimental class (696,64) and the control class (516,66). The level of significance was set up 0,05 with 18 degree of freedom ( (df) = Nx + Ny – 2 = 10 + 10 – 2). The result of data analysis indicates that tcounted (2,573) which was higher than ttable (2,153),it means that the hypothesis of the research was accepted. Thus, there was significant score improvement of using talking stick strategy to the tenth grade students at SMA Negeri 1 Kasimbar.